2018
DOI: 10.1051/0004-6361/201832937
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal photospheric flows trigger a filament eruption

Abstract: Context. A large filament composed principally of two sections erupted sequentially in the southern hemisphere on January 26 2016. The central, thick part of the northern section was first lifted up and lead to the eruption of the full filament. This event was observed in Hα with the Global Oscillation Network Group (GONG) and Christian Latouche IMageur Solaire (CLIMSO), and in ultraviolet (UV) with the Atmospheric Imaging Assembly (AIA) imager on board the Solar Dynamic Observatory (SDO). Aims. The aim of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
(59 reference statements)
3
12
0
Order By: Relevance
“…A detailed investigation and confirmation of our scenario is not possible without proper MHD modelling, which is beyond scope of this paper. Our findings are consistent with those of Roudier et al (2018), who concluded that the filament destabilisation was caused by the joined action of the differential rotation shear and convergent flows towards the filament.…”
Section: Discussionsupporting
confidence: 93%
“…A detailed investigation and confirmation of our scenario is not possible without proper MHD modelling, which is beyond scope of this paper. Our findings are consistent with those of Roudier et al (2018), who concluded that the filament destabilisation was caused by the joined action of the differential rotation shear and convergent flows towards the filament.…”
Section: Discussionsupporting
confidence: 93%
“…L1 is used to image the full disk of the sun (top left panel of Fig. 3) and essentially to capture and watch the evolution of filaments (Roudier et al, 2018). L1's resulting effective focal length is 1350 mm.…”
Section: L1 and L2 Solar Refractorsmentioning
confidence: 99%
“…Some filament material falls to the filament ends and to an intermediate footpoint. Roudier et al (2018) studied triggers of this filament eruption. They concluded that the filament was destabilized by converging photospheric flows below it, which initiated an ascent of the middle section of the filament up to the critical height of the torus instability.…”
Section: January 26 Eventmentioning
confidence: 99%